Banks and The Global Financial Crisis: What Did They Say about Their Risk Management Before The Crisis? How Did This Change Afterwards? Use Information from Their Reports and Accounts - Kurian, John (2012)
The recent Financial Crisis in 2007-2008 has proved the world to be an eye opener to the existence of the Black swan theory. In the case of banks which deals with the public money and act as the backbone of the whole financial system, the catastrophe has brought a good moral. This thesis surf through the incipient crisis scenarios and further penetrating through the factors that propelled the crisis, till the aftermath of the turbulence. Causalities and impacts on the “Too Big to Fail” giants in the banking sector and the lessons we can pass on to the next generation are also explained. Merely having the trump card will not lead to victory unless right strategy is applied. Similarly, possessing highly sophisticated models and complex methods couldn’t rescue the giants due to weak risk management and flawed strategies.